The test-retest reliability of the Opiate Treatment Index in nyaope users in Johannesburg - Kelebogile Pitsoane; Nirvana Morgan; Sumaya Mall (South African Journal of Psychiatry, 2024)
Background: Epidemiological studies suggest that nyaope, a heroin-based drug, is widely used in South Africa. Yet few reliable research tools are available to assess treatment outcomes of users. The Opiate Treatment Index (OTI), a tool developed in Australia, could potentially facilitate research on context-specific South African treatment outcomes. However, we know little of its test-retest reliability.